(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Pomegranate (Punica granatum) peel is rich source of dietary fiber and bioactive compounds, hence, attempt was made to see the effect of dried dried pomegranate peel powder (DPPP) on the bioactive constituents and micro structural quality of chapatti. Chapatti dough prepared from 5, 7.5 and 10% DPPP was examined for dough stickiness, dough strength and dough hardness. With increased level of DPPP, dough stickiness increased due to increased water absorption capacity whereas dough strength and dough hardness decreased due to presscence of large amounts of dietary fibre in DPPP. Chapatti incorporated with 10% DPPP showed DPPH radical scavenging activity up to 64.4% showing presence of active antioxidants. The microstructure of chapatti prepared from dough added with 10 % starch granules, fibrous structures and protein bodies were adhered to starch granules and protein matrix while in the control protein is seen either in association with starch granules or as clusters of storage protein. Chapatti’s prepared from DPPP had softer chapatti.